Multicellular dosimetry in voxel geometry for targeted radionuclide therapy. - Malaroda, A; Flux, G; Buffa, F; Ott, R (2003)
A software package to investigate absorbed doses and dose-rates at the cellular and multicellular scale has been developed that considers two- and three-dimensional activity distributions and makes use of analytical representations of the point-dose kernels for (131)I, (32)P, and (90)Y. This software allows cell assemblies to be simulated by definition of the number, size, and geometry of cells and their nuclei, and radionuclide uptake can be specified to occur within the nucleus, the cytoplasm, at the membrane, or within the extracellular space. The software has been validated at a cellular scale by comparison with results obtained using spherical geometry, as found in the literature. At a multicellular scale, comparisons were made with a Monte Carlo simulation in voxel geometry. The software has been designed to work within a user-defined voxel geometry. This geometry is useful not only to simulate complex cell assemblies and realistic heterogeneous radionuclide distributions, but will also allow the use of histological and autoradiographic data. Absorbed dose distributions for a single cell calculated using this code varied significantly with activity localization within the cell, and to a lesser extent, with the cellular geometry. At a multicellular level, a two-dimensional heterogeneous activity distribution inferred from a two-dimensional image of a slice throughout a spheroid was used to calculate a dose-rate distribution. This resulted in a heterogeneous dose-rate delivery even for longer-range radionuclides such as (90)Y and (32)P.